Distributed and jamming-resistant channel assignment and routing for multi-hop wireless networks - Jembre, Yalew Zelalem; Choi, Young June (IEEE Access, 2018)
We are becoming more reliant on multi-hop wireless networks (MWNs) for public safety, tactical/military, and last mile Internet communications. The architecture of an MWN can be flat, as in ad-hoc networks or hierarchical, as in mesh or sensor networks. Today, the lower cost and smaller size of radios enables multiple radios to exist in a device. Hence, simultaneous transmissions on orthogonal channels are possible, which multiplies the performance of MWNs. However, an efficient communication is only possible if every device has reliable connection. A connected MWN can be created using a meticulous channel assignment (CA) scheme that reduces congestion and interference. In addition, CA needs to handle jamming attacks. The medium access control (MAC) layer is responsible for CA related tasks. However, CA results in topology changes that affect routing decisions taken at the routing layer, which could lead to unreliable network. This strong interrelationship requires a cross-layered approach to ensure reliable connectivity. In this paper, we formulate this cross-layer problem as network-path cost optimization. Because the problem is NP-hard, we propose a dynamic and distributed heuristic CA and routing scheme that is applicable for both flat and hierarchical MWNs and that is also resistant to jamming attacks. We call it distributed jamming resilient channel assignment and routing (DJ-CAR) scheme. The performance of DJ-CAR, with that of existing schemes, is compared using an OPNET simulator.
Keywords: Channel allocation; Channel Assignment; cross-layered; Multi-radio; Multihop; Performance evaluations; Routing; Channel assignment; cross-layered; jamming; multi-hop; multi-radio; routing